2021
DOI: 10.3389/fphys.2021.576917
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Candidates to Do Fresh Embryo Transfer in Those Using Oral Contraceptive Pretreatment in IVF Cycles

Abstract: ObjectiveConcern regarding the adverse impact of pretreatment of oral contraceptives (OC) prior to ovarian stimulation for in vitro fertilization (IVF) on pregnancy outcome has been debated. We investigated factors that may be associated with live birth rate (LBR) in fresh embryo transfer cycles after OC pretreatment.MethodsA retrospective study was conducted at the Reproductive Center of Ren Ji Hospital, Shanghai, China. 814 women aged 20–35 years undergoing their first autologous IVF cycle and fresh embryo t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Each patient received individual doses of gonadotropins, FSH, and/or human menopausal gonadotropin, starting on day 2 or 3 of the menstrual cycle. Recombinant human chorionic gonadotropin (hCG) was administered to the patient to induce final follicular maturation when the dominant follicles reached a diameter of ≥ 18 mm ( 26 , 27 ). With respect to the standard clinical practice of oocyte retrieval at the Center for Reproductive Medicine, Renji Hospital, all accessible follicles were punctured and aspirated using a 16-gauge needle under ultrasound guidance 35–37 h after the administration of recombinant hCG.…”
Section: Methodsmentioning
confidence: 99%
“…Each patient received individual doses of gonadotropins, FSH, and/or human menopausal gonadotropin, starting on day 2 or 3 of the menstrual cycle. Recombinant human chorionic gonadotropin (hCG) was administered to the patient to induce final follicular maturation when the dominant follicles reached a diameter of ≥ 18 mm ( 26 , 27 ). With respect to the standard clinical practice of oocyte retrieval at the Center for Reproductive Medicine, Renji Hospital, all accessible follicles were punctured and aspirated using a 16-gauge needle under ultrasound guidance 35–37 h after the administration of recombinant hCG.…”
Section: Methodsmentioning
confidence: 99%
“…Among 115 patients in a prospective study, Garcia-Velasco et al [18] demonstrated that a shorter period of COCs 12-16 days had no effect on pregnancy outcomes in regularly cycling patients who underwent IVF. Most of the studies examining the impact of precycle COC use have been performed in normal responders and excluded individuals with PCOS [19].…”
Section: Key Pointsmentioning
confidence: 99%
“…Patients with endometrial thickness less than 8 mm experienced lower implantation and pregnancy rate [ 12 ]. Significantly, recent studies have proved that patients treated with GnRH-ant protocol developed a remarkably thinner endometrial thickness than patients treated with GnRH-a protocol [ 13 , 14 ]. These results implied that one of the adverse effects of GnRH-ant on endometrium was to weaken endometrial thickness.…”
Section: Introductionmentioning
confidence: 99%